On the Oosterhoff dichotomy in the Galactic bulge – II. Kinematical distribution. Issue 3 (31st May 2019) - Prudil, Z; Dékány, I; Grebel, E K; Catelan, M; Skarka, M; Smolec, R
ABSTRACT: We present a kinematical study of RR Lyrae stars associated with two Oosterhoff groups in the Galactic bulge. We used data published in the first paper of the series, plus proper motions from the Gaia Data Release 2, and radial velocities from the literature. A 6D kinematical and spatial solution was obtained for 429 RR Lyrae stars. We use a model of the Galactic gravitational potential to infer stellar orbits. We did not find a difference between the Oosterhoff groups in the individual components of the space velocity. We report that foreground and background stars with respect to the Galactic bulge stand out in the mean V velocity component, which we interpret as a sign of the Galactic rotation. The movement of the studied stars in the central region of the Galactic bulge is consistent with random motions expected for a classical bulge component. From the orbital integration, we estimate that 8 per cent of the RR Lyrae stars are halo interlopers currently located in the Galactic bulge. The majority of the stars' orbits are within a 3 kpc radius from the Galactic bulge. The fraction of Oosterhoff II stars increases with increasing Galactic latitude, as well as towards longer orbital periods. We found several RR Lyrae stars with high space velocities, one of which has an extremely long orbital period of ∼1 Gyr. We conclude that based on their kinematics, the vast majority of the stars in our sample do not seem to contribute to the boxy/peanut component of the Galactic bulge.